Detection of Nontuberculous Mycobacterium by Real Time PCR from Variety of Clinical Specimens (Pulse, 2017)
Aim: Nontuberculous mycobacterium (NTM) causes many types of infections including respiratory and non-respiratory infections such as skin and soft tissue infections, lymphadenitis, meningitis, gastro-intestinal infections, disseminated infections and even intravenous catheter-related infections. Increasing incidence of NTM is reported worldwide in last decade. However, incidence of NTM in Bangladesh is not known as detection of NTM is not undergoing in Bangladesh which is necessary to know as these NTM species are resistant to first-line anti-TB drugs and, when mistaken for M. tuberculosis, give rise to erroneous identification of multidrug-resistant TB (MDR-TB). We wanted to know the existence of NTM from various clinical specimens including tissues from tuberculosis suspected patients visited in Apollo Hospitals Dhaka in 2013 to 2015.Material and Method: Sample processing, DNA extraction and real time PCR (polymerase chain reaction) were done according to the commercial LyteStar TB/NTM PCR kit developed by Altona Diagnostics, Germany. The target DNA sequences are amplified with IS61 10-specific primers for MTB complex and ITS-specific primers for NTM. Probes specific for MTB complex and NTM DNA are labeled with fluorophore dye FAM and HEX, respectively. We have analyzed 579 clinical specimens from tuberculosis suspected patient.Result: Among 579 specimen different types of tissues were 201 and histopathology data were available for 166 cases. In tissues NTM was detected by PCR in 3 1(19%) cases, 8 of which were compatible with histopathology findings and rest 23 cases showed no evidence of granulomatous lesion. We analyzed 378 different varieties of clinical specimens such as sputum, bronchial lavages, body fluids, pus and swabs. Among 378 samples 215 samples were requested for AFB staining. NTM was detected by PCR in 19(8.8%) samples and out of 19 NTM positive specimens only one was AFB positive.Conclusion: This is the first report in the country about detection of NTM in variety of clinical specimens and warrants further elaborate investigation. Our results showed that PCR is an effective tool for the rapid identification of NTM from tissues and AFB negative clinical specimens having suspicion for mycobacterial infection.Pulse Vol.9 January-December 2016 p.15-21